Byproducts, Waste Biomass and Products to form Green Diesel and Biocrude Oils (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book provides a collection of research and review articles useful for researchers, engineers, students and industry experts in the bioenergy field. The practical and valuable information can be utilized for developing and implementing renewable energy projects, selecting different waste feedstocks, technologies, and products. A detailed insight into advanced technologies such as hydrothermal liquefaction, torrefaction, and supercritical CO2 extraction for making sustainable biofuels and chemicals is provided. A case study on food waste-to-energy valorization processes in Latin America provides experts’ insights to promote a circular economy.